Is the development of desalination compatible with sustainable development of the Arabian Gulf?. (December 2021) - Le Quesne, W.J.F.; Fernand, L.; Ali, T.S.; Andres, O.; Antonpoulou, M.; Burt, J.A.; Dougherty, W.W.; Edson, P.J.; El Kharraz, J.; Glavan, J.; Mamiit, R.J.; Reid, K.D.; et al.
Abstract: The development of desalination has been essential to the rapid economic development of the countries bordering the Arabian Gulf. The current production capacity of sea water desalination plants drawing water from Gulf is over 20 million m 3 day −1, which may rise to 80 million m 3 day −1 by 2050. Whilst supporting aspects of sustainable development related to water and sanitation, desalination impacts the marine environment through impingement and entrainment of organisms in intakes, and through thermal, brine and chemical discharges. This may compromise other objectives for sustainable development related to sustainable use of the oceans. Under business as usual scenarios, by 2050, the impact of individual desalination plants will combine causing a regional scale impact. Without mitigating actions to avoid the business as usual scenario, by 2050, desalination in combination with climate change, will elevate coastal water temperatures across more than 50% of the Gulf by at least 3 °C, and a volume of water equivalent to more than a third of the total volume of water between 0 and 10 m deep will pass through desalination plants each year. This will adversely impact the coastal ecosystem of the Gulf, with impacts on biodiversity, fisheries and coastal communities and may cause potential loss of species and habitats from the Gulf. Given the significant implications of these preliminary findings, and in light of the precautionary approach to management, it is recommended that mitigating options addressing behavioural, regulatory and technological change are rapidly evaluated and implemented to avoid the development of desalination in the region along a business as usual pathway, and multidisciplinary research studies should be conducted to reduce uncertainty in predictions of future impacts. Graphical abstract: Unlabelled Image Highlights: Desalination in the Arabian Gulf both supports and threatens sustainable development. Impacts of individual desalination plants will combine to cause regional impact. Desalination will adversely impact biodiversity, fisheries, and coastal communities. Desalination will magnify the impact of climate change on the Gulf. Minimising impacts requires behavioural, regulatory, and technological development.